A retrospective case series on the usefulness of fractionated stereotactic radiotherapy for benign intracranial tumors - Mario Ammirati, M.D., M.B.A; Roberto Colasanti, M.D.; Tariq Lamki, M.D.; Al-Rahim Abbasali Tailor, M.D.; Andrew Kalnin, M.D.; Wayne Slone, M.D.; John Grecula, M.D. (Interdisciplinary Neurosurgery, 2019)
Introduction: Conventional radiation therapy has been progressively replaced by fractionated stereotactic radiotherapy (FSRT) and single fraction radiosurgery for dealing with benign intracranial lesions. Purpose of our study is to investigate the safety and efficacy of FSRT in a series of patients with benign intracranial tumors. Methods: 31 patients with benign intracranial lesions treated with FSRT between 2006 and 2014 were retrospectively reviewed. Indications for treatment included post-operative residual tumor growth or symptomatic exacerbation in patients in whom surgery was not indicated. A clinical and radiological outcome evaluation was performed. Univariate analysis was executed to identify predictors for post-treatment neurological function and radiological tumor control. Results: Median age was 62 years (range 22–82). The lesions treated included 20 meningiomas, 2 vestibular schwannomas, 7 pituitary adenomas, 1 craniopharyngioma, 1 jugular-tympanic paraganglioma. Median clinical target volume was 14.59 cm3 (range 0.43–159.06) and median planning treatment volume was 18.16 cm3 (range 0.81–217.24). Median total dose was 45 Gy (range 25–54), and median daily fraction 4 Gy (range 1.8–9). At a median follow-up of 78 and 50 months, respectively clinical and neuroradiological, no tumor had larger dimensions, and only one lesion changed in a way other than size determining a concomitant clinical worsening. Other three patients deteriorated without evidence of radiological progression. Conversely, 12 patients improved clinically. No significant predictor for post-treatment neurological function or radiological tumor control was found. Conclusion: FSRT may represent, when indicated, a safe and effective treatment modality for benign intracranial tumors, especially for large/irregular lesions. Keywords: Clinical outcome, Fractionated stereotactic radiotherapy, Intensity-modulated radiotherapy, Intracranial benign lesions, Tumor progression, Radiotherapy